Specifics of the Emotional Response of Patients Suffering From Major Depressive Disorder to Imagined Basic Tastes of Food - Jarutiene, Laura; Adomaitiene, Virginija; Steibliene, Vesta; Juodeikiene, Grazina; Cernauskas, Darius; Klupsaite, Dovile; Lele, Vita; Milasauskiene, Egle; Bartkiene, Elena (Frontiers in Psychology, 2022)
Nowadays, the major depressive disorder (MDD) is a common disease that negatively affects the life quality of many people around the world. As MDD symptoms are closely related with the changes in food and eating, the relation between patients’ emotional responses and food tastes could be used as criteria for diagnostic. Until now, studies on the emotional response to different food tastes for patients affected by MDD have been poorly described in literature. Therefore, the aim of this study was to evaluate the emotional response of patients suffering from MDD to the imagined different food tastes and to compare the results with a control group. Emotional responses in tested participants were induced by using cards with words of basic food tastes such as “sweet“, “salty“, “bitter“, “sour“ and “neutral“. The assessment of emotional response was performed with FaceReader6 software. The outcome of this study showed that participants with MDD expressed lower ‘‘happy’’ and ‘‘contempt’’ and higher “surprised” emotions, along with a higher negative valence mean, in comparison with controls for all tested basic tastes of food (p ≤ 0.05). When Likert scale was used, significant differences (p ≤ 0.001) in response were only found for “sour“ and “salty“ imaginary tastes between healthy group and patients with MDD. The findings of this study provide the additional data on food–associated emotion analysis of MDD patients and could be useful for the further development of the contactless method for early diagnosis of MDD.